The Ecology of Internet Use during Middle Childhood: Physical, Social, Emotional and Cognitive Development - Johnson, Genevieve (Association for the Advancement of Computing in Education, 2012)
The ecological techno-microsystem provides a comprehensive theoretical framework for organizing the effects of internet use on child development. Ninety children in grades 3 through 6 rated their uses of the internet. Parents and teachers rated each child’s level development. Using stepwise regression analysis, the eight measures of child development (i.e., social, emotional, physical and cognitive development rated by parents and teachers) were treated as dependent variables and child rating of internet use (i.e., five items for each of home, school and community use) were treated as independent variables. Various patterns of internet use related to various patterns of child development across all domains, although the most enduring relationships were between internet use and cognitive and social development. Results provide preliminary support for the ecological techno-microsystem.